2011
DOI: 10.1093/intimm/dxr110
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 and IL-22 enhance skin inflammation by stimulating the secretion of IL-1β by keratinocytes via the ROS-NLRP3-caspase-1 pathway

Abstract: These results indicate that cytokines from T(h)17 cells may potentiate IL-1β-mediated skin inflammation and result in phenotypic alterations of keratinocytes via a feedback mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 37 publications
6
103
1
2
Order By: Relevance
“…We (25,40), and others (29,41) have demonstrated the importance of the Th17 pathway in defense against S. aureus skin infection. For example, Cho et al reported that T cell production of IL-17 but not of IL-22 promoted neutrophil recruitment in defense against S. aureus in a mouse model of SSSI (29).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We (25,40), and others (29,41) have demonstrated the importance of the Th17 pathway in defense against S. aureus skin infection. For example, Cho et al reported that T cell production of IL-17 but not of IL-22 promoted neutrophil recruitment in defense against S. aureus in a mouse model of SSSI (29).…”
Section: Discussionmentioning
confidence: 82%
“…Rather, IL-22 regulates skin barrier integrity and protection from pathogens by acting on epithelial cells by several mechanisms. First, it prompts epithelial cells to secrete proinflammatory cytokines for leukocyte recruitment and activation (41,51). Second, it induces epithelial cell proliferation during wound healing (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…CP-456,773 efficacy in the imiquimod cream-induced skin inflammation model might result from direct prevention of imiquimod cream-induced NLRP3 inflammasome activation and IL-1b release, because imiquimod stimulation (with LPS priming) is capable of activating the NLRP3 inflammasome and IL-1b release from mast cells (45,46). Alternatively, as IL-17 and IL-22 are present and contribute to skin disease in this model, CP-456,773 may act by preventing IL-17-and IL-22-mediated activation of the NLRP3 inflammasome in keratinocytes (42,47). Reduced skin inflammation and dermal thickness induced by imiquimod cream has been observed in caspase-1-deficient mice (47).…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, as IL-17 and IL-22 are present and contribute to skin disease in this model, CP-456,773 may act by preventing IL-17-and IL-22-mediated activation of the NLRP3 inflammasome in keratinocytes (42,47). Reduced skin inflammation and dermal thickness induced by imiquimod cream has been observed in caspase-1-deficient mice (47). However, in a recent publication from Rabeony et al (48), imiquimod cream-induced skin inflammation was not reduced in NLRP3-, caspase-1-, and ASC-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Since ROS and RNS (particularly nitric oxide, NO) have been shown to stimulate cytokine production in epithelial cells via activation of MAPKs (p38, ERK), JNKs, NF-κB, AP-1, soluble guanylate cyclase (sGC)/protein kinase G (PKG) [141][142][143][144][145] and recently NLRP3 inflammasome pathways, 146 it is possible that laser adjuvants can mediate activation (phosphorylation) of these pathways via ROS generation. Endogenous or exogenous ROS and NO have been shown to modulate the function of skin cells including keratinocytes [147][148][149][150] and mast cells.…”
Section: Photochemical Effectsmentioning
confidence: 99%